Approaching an Intersection: Pragmatic Competence and Being a University Student - de Man, George (AMERICANA E-journal of American Studies in Hungary, 2024)
One of the more familiar challenges of teaching first-year university students is fostering their initiative to take part in class discussion. In the EFL classroom, discussion activities are rightly valued as opportunities for language practice. Less obvious, in contrast, may be the ways that the process of acculturation to college classroom norms intersects with second language difficulties, especially among f irst-generation college students who comprise a sizable demographic in the Hungarian university population. Pragmatics instruction, it will be argued, has a role to play in helping empower students to express their ideas and opinions in the company of their peers and instructors. However, supplying students with a lexical “toolkit” and peer-to-peer scenarios is only a first step in this direction. Indeed, it is precisely because the college experience is for many “first gens” a form of culture shock that the norm-disrupting potential of North American humor can be as important as modeling the myriad ways English speakers can verbally negotiate awkward or unfamiliar situations. Best practices for supporting first-year student engagement and success, as piloted at U.S.-based higher education institutions will also be explored.